CIPHERTEXT DESTRUCTION IN CLOUD STORAGE - S N, Ms. Rekha; Priya M, Ms. Guru (IJRDO -Journal of Computer Science Engineering, 2016)
In cloud services, users will frequently be required to reveal their personal sensitive information which could be stored in the cloud which is used for different purposes. However, in a cloud storage network, the servers are easily prone to strong attacks and also commonly experience software/hardware faults. As such, the private information could be under risk in an untrusted environment. Given that the personal sensitive information is usually out of user’s control in most cloud-based services, ensuring data security and privacy protection with respect to untrusted storage network has become a formidable challenge in research. To address these challenges, in this paper we propose a selfdestruction system, named Cloud Sky, which is able to enforce the security of user privacy over the untrusted cloud in a controllable way. Cloud Sky exploits a key control mechanism based on the attribute-based encryption (ABE) and takes advantage of active storage networks to allow the user to control the subjective life-cycle and the access control polices of the private data whose integrity is ensured by using HMAC to cope with untrusted environments. The feasibility of the system by its performance and scalability is demonstrated by experiments on a large-scale storage network.